Behavioral Medicine: A historical review. - Baños-Chaparro, Jonatan (2022)
Behavioral medicine is an interdisciplinary field that involves behavioral and biomedical sciences towards the study of behavior, with the aim of preventing and treating physical illnesses and improve the human being’s health levels. The manuscript examines the evolution of the concepts of health and disease throughout the last century is indicated in principle. In this process, the events that contributed to the emergence of behavioral medicine and those that happened during its first years of consolidation, are mentioned. Its current development, substantiated in evidence- based physical and digital environments, and the interest in and relevance of how to translate this evidence in the formulation of public health policies, are also explained. The purpose of this review is to extend the principles and practice of behavioral medicine in the Spanish-speaking community, exposing the relevance of this discipline in the public health field.